Penerapan Pendekatan Realistic Mathematics Education untuk Meningkatkan Kemampuan Berpikir Kreatif Matematika Siswa Kelas IX.E SMP Negeri 12 Mataram - Istiroha, Istiroha (YASIN, 2023)
The purpose of this study was to find out the application of the Realistic Mathematics Education (RME) approach to improve the Mathematical Creative Thinking Skills of Class IX.E Students of SMP Negeri 12 Mataram Odd Semester 2022/2023 Academic Year. The research subjects were all 32 students in class IX.E at SMP Negeri 12 Mataram for the academic year 2022/2023 consisting of 15 boys and 17 girls. The results showed that: 1) In this study the teacher's activity in managing learning was measurable and it could be seen that the teacher was able to manage learning activities well. Teacher activities in managing learning using the Realistic Mathematics Education (RME) approach between cycle I, cycle II and cycle III experienced an increase, namely with a percentage value of 61.33% (good enough) in cycle I and increased in cycle II to 74.28%. (good) in the third cycle increased with a percentage of 88.88% (very good); 2) Student activity in participating in the learning process is measurable and it can be seen that students are active and in control. Student activities in participating in learning using the Realistic Mathematics Education (RME) approach between cycle I, cycle II and cycle III experienced an increase, namely with a percentage value of 65.33% (enough) in cycle I and increased in cycle II to 78.57% ( good) in the third cycle it increased with a percentage of 85.33% (very good); 3) Student learning outcomes through the application of the Realistic Mathematics Education (RME) approach can improve student learning outcomes in Mathematics learning for Class IX.E SMP Negeri 12 Mataram. This can be seen clearly from the test data on student learning outcomes through the Realistic Mathematics Education (RME) approach. The pre-action quiz questions obtained 34.38% and the first cycle was 59.36%, the percentage value of students was included in the (good enough) category, while the RPP quiz questions cycle II reached 78.13% including the (good) category, and then in the lesson plan quiz questions for cycle III it reached 87.50% more than cycles I and II and the percentage of students was included in the (very good) category.